2018
DOI: 10.22605/rrh4453
|View full text |Cite
|
Sign up to set email alerts
|

A collaboration with local Aboriginal communities in rural New South Wales, Australia to determine the oral health needs of their children and develop a community-owned oral health promotion program

Abstract: Aboriginal children living in rural and remote communities in NSW experience high rates of dental caries. Oral health promotion is urgently required to reduce the burden of dental caries and should address oral hygiene behaviours, fluoride use and access to healthy foods and drinks. Note: This article uses the term 'Aboriginal people' when referring to the first peoples of Australia. This term is inclusive of Australian Aboriginal and Torres Strait Islander people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 0 publications
4
21
0
2
Order By: Relevance
“…Some studies with Australian Aboriginal communities revealed that the effectiveness of a health program is linked to how well the program adopts the community's cultural practices, knowledge, and involves community members to participate and lead the program. [50][51][52][53] These factors highlight the importance of the community to be directly involved with the development of the training program. In the context of the broader PAR program of research, the team will need to build the training program integrating the participants' suggested content and delivery, using the insights gained through these focus groups.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies with Australian Aboriginal communities revealed that the effectiveness of a health program is linked to how well the program adopts the community's cultural practices, knowledge, and involves community members to participate and lead the program. [50][51][52][53] These factors highlight the importance of the community to be directly involved with the development of the training program. In the context of the broader PAR program of research, the team will need to build the training program integrating the participants' suggested content and delivery, using the insights gained through these focus groups.…”
Section: Discussionmentioning
confidence: 99%
“…The second theme identi ed was socio-economic status This theme comprised economic status and social and cultural status of the Indigenous Australian population that poses many challenges in the utilization of oral health services. Financial concerns of the families [23,35], transportation problems [8,29] and living in remote areas [39] were among some of the economic challenges of oral health utilization. Cultural barriers included di culty in communication [36], language barriers [29] and low selfe ciency [34].…”
Section: Geographic Barriers In Accessing Oral Health Servicesmentioning
confidence: 99%
“…In the focus group, RAOs raised concerns about water quality in many regional and remote settings, citing problems such as yellow bore water, high levels of lead in water and 'poisoned' water (such as contamination with per-and polyfluoroalkyl substances in Katherine, Northern Territory (50) ). Previous research suggests that tap water is perceived as 'unhealthy' in some settings (51) , including due to a history of water quality problems (49) . RAOs explained that, when concerned about water taste or safety, many people avoid drinking tap water and buy bottled water or other beverages; when bottled water is the same price as SSB, people may opt for SSB.…”
Section: Factors Associated With Sugar-sweetened Beverage Consumptionmentioning
confidence: 99%